Investigation of the Evolution of Magnetic and Acoustic Characteristics as a Result of Annealing of Cold-Deformed Nickel - Kostin Vladimir (EDP Sciences, 2021)
The change in the magnetic and acoustic properties of nickel as a result of cold deformation and subsequent annealing is investigated. It was found that annealing leads to very significant changes in the magnetic and acoustic properties of nickel. The coercive force decreases 50 times with an increase in the annealing temperature to 800 °C. The Rayleigh coefficient, which characterizes the mobility of domain walls, monotonically increases by a factor of 20 over the entire investigated range of annealing temperatures. The greatest changes in the velocity and damping of longitudinal ultrasonic vibrations occur in the range of recrystallization temperatures. It is shown that to diagnose the structure and magnitude of residual stresses in nickel, it is advisable to determine its magnetic and acoustic parameters.